Anteaters Don't Dream and Other Stories - Hawes, Louise (Book collections on Project MUSE., 2007)
In Anteaters Don't Dream and Other Stories, Louise Hawes deftly portrays lovers at the end of their patience, marriages on the verge of decline, children reeling from abuse, and parents devastated by loss. But many of these stories have a sardonic, humorous edge as well: in the title story, a jaded architect learns to take his dream life more seriously when a female co-worker threatens his career. In "Mr. Mix Up," a mother becomes infatuated with the clown at her son's birthday party. In "My Last Indian," a menopausal woman goes native. And in "Salinger's Mistress," a young woman lies about.